2003
DOI: 10.1161/01.cir.0000070420.51787.a8
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Remodeling and Ventricular Arrhythmias After Myocardial Infarction

Abstract: Background-The relation between left ventricular (LV) remodeling and ventricular arrhythmias after myocardial infarction is poorly documented. We investigated the relations between LV size, hypertrophy, and function and ventricular arrhythmias in 263 patients from the Survival and Ventricular Enlargement (SAVE) study, using quantitative 2D echocardiography and ambulatory ECG monitoring after myocardial infarction. Methods and Results-Transthoracic 2D echocardiograms and arrhythmia monitoring were performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(119 citation statements)
references
References 37 publications
6
109
0
4
Order By: Relevance
“…[2][3][4][5][6] At the infarcted region, alterations in myocardial composition and structure occur after MI 6,7 and can lead to infarct thinning and expansion. 1,4 -7 Because the MMPs are enzymes that influence myocardial remodeling, 8 -16 the goal of the present study was to examine the relation between MMP activation and infarct expansion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6] At the infarcted region, alterations in myocardial composition and structure occur after MI 6,7 and can lead to infarct thinning and expansion. 1,4 -7 Because the MMPs are enzymes that influence myocardial remodeling, 8 -16 the goal of the present study was to examine the relation between MMP activation and infarct expansion.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The summation of cellular and extracellular events that occur in the post-MI period results in changes in LV geometry and has been called "infarct expansion." [3][4][5][6] Past studies have demonstrated that a structural determinant of infarct expansion is extracellular remodeling. 1,5,6 A family of proteolytic enzymes that have been implicated in tissue remodeling are the matrix metalloproteinases (MMPs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Remodeling is linked to heart failure progression and is associated with poor prognosis following myocardial infarction. Ventricular dilation following myocardial infarction is an important predictor of mortality [6] and adverse cardiac events [7], including the development of heart failure and ventricular arrhythmias [8], [9]. The extent of adverse remodeling depends on the size of the infarct but is also directly affected by the pathologic and structural changes associated with infarct healing.…”
Section: Introductionmentioning
confidence: 99%
“…LV diameter has been shown to be independently predictive of SCA and to have an additive effect with LVEF on predicting SCA risk 34, 35. Two studies, 1 in patients post–myocardial infarction36 and the other in patients with severe LV dysfunction,37 found that increased LV size was predictive of ventricular arrhythmias and frequent premature ventricular contractions (PVC). This association was further supported in a study that found reduction of LV end‐systolic size in patients undergoing cardiac resynchronization therapy reduced occurrence of PVCs and VT/VF events 38.…”
Section: Discussionmentioning
confidence: 99%